Lo status di rifugiato religioso nel diritto internazionale ed europeo: la sinergia tra Nazioni Unite, Unione Europea e Consiglio d’Europa = The status of religious refugee in international and European law : the synergy among United Nations, European Union and the Council of Europe - Ferrari, Daniele (Vergentis, 2021)
The concept of religious refugee represents today the main instrument of protection of religious freedom. Starting from this observation, the contribution reconstructs the notion of religious refugee in international and European law through the institutional collaboration processes between the United Nations, the European Union and the Council of Europe. In these terms, the definition of religious refugee is reconstructed: in the Geneva Convention; to explicit references to the UN model in European law; similar methods of work expressed by international and European institutions.